Social media-based Health Education plus Exercise Program (SHEEP) to improve muscle function among young-old adults with possible sarcopenia in the community: A feasibility study protocol - Ya Shi; Emma Stanmore; Lisa McGarrigle; Chris Todd (PLoS ONE, 2025)
Background Despite the comparatively high prevalence of possible sarcopenia among young-old adults in the community, there is currently no available and effective social media-based intervention to increase the awareness and change the behavior of the target population to prevent sarcopenia. Using co-design methodology, we developed a multicomponent intervention strategy of health education and exercise for sarcopenia prevention utilizing the TikTok platform. Objectives The primary purpose of this study is to examine the feasibility and acceptability of the social media-based intervention to enhance muscle function in community-dwelling young-old adults with possible sarcopenia. Methods This protocol outlines the entire research procedure for a prospective single-arm pre-post feasibility study employing a mixed-method design, which will be conducted between May 2024 and September 2024. Thirty-five older adults aged 60–69 years with possible sarcopenia will be recruited from two communities in Changsha, China. Using the TikTok platform, participants will be required to view a total of seven health education videos in the first week, and each video lasts four to six minutes. Then, participants will receive six-week multi-component exercise through TikTok, with at least three sessions/week, 30 minutes/session, and moderate intensity. Data collection will be conducted in baseline, week 1, 4, 7, 10 and 13. The primary outcomes will include evaluating recruitment capability, data collection procedure, outcome measurement, intervention procedures’ acceptability, researchers’ ability to manage and implement the study, among others. The secondary outcome is to compare standard measures for muscle function (e.g. handgrip strength, skeletal muscle mass, physical performance), body composition (e.g. body fat, body mass index, bone mineral), and other measures (e.g. perceived knowledge, personal motivation, behavioral skills). Finally, all participants will be offered a semi-structured interview to assess their in-depth experiences with the intervention and research process. Discussion This study will be the first social-media based multicomponent intervention program for community young-old adults with possible sarcopenia to improve their muscle function, awareness and behavior of preventing sarcopenia. Findings will generate new evidence regarding the use of social media in health education for improving awareness of sarcopenia prevention, as well as the feasibility of using social media to influence participants’ behavioral changes through exercise. This may help researchers identify ways to optimize acceptability and efficacy of the SHEEP intervention for the targeted population. Trial registration ISRCTN registry, ISRCTN17269170, Registered 14 September 2023.